Base Line Data of Native Cattle (Grade Ongole Cattle) in the Special District of Yogyakarta - Hardjosoebroto, Wartomo; Atmodjo, Supiyono P.; Mulyadi, Hasyim (Faculty of Animal Husbandry Universitas Gadjah Mada, 1981)
This research had the objective of developing basic data on native acttle (Grade Ongole cattle) in the Special District of Yogyakarta. The research was carried on for four-year period, July 1977 through June 1981. It made use of 1000 mature cows located at Playen (Dist. Gunung Kidul) and Cangkringan (Dist. Sleman). Collection of data was by 20 persons recruited as cadres. Data was collected once each two weeks and the animal were weighed once each three months. In thes research the average call crop born was 36.0% with 54.24% of the calves born being females. 61.48% of the calves were born in the period between April to September. The reason for this is still unknown. The average interval bettween calving of cows calving more than once during the study was 18.6 months. Firs mating after calving averaged 239.5 days with 1.37 services per conception. Weaning age averaged 241.4 days. Annual death rates were 1.02% for calves and 2.67% for cows. The average daily gain for the adult non-pregnant cows was 0.085 kg per day. During the 4-year period, 357 mature cows were sold and 233 purchased. From the above data it can be concluded that the calving rates of native cattle in the above two locations were low, and that this may be related to genetic factors and poor management.